2015
DOI: 10.2147/pi.s77566
|View full text |Cite
|
Sign up to set email alerts
|

Supporting parents of children with type 1 diabetes mellitus: a literature review

Abstract: Abstract:This review provides the reader with an integrative view of the literature on the challenges families of patients with type 1 diabetes mellitus face, and the interventions proposed in research and practice to facilitate their coping and efficacy in supporting patient care. We present background information regarding the condition and the general challenges it poses, and then focus on younger patients and their families, while reviewing the literature and emerging patterns describing pitfalls and propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Achievement of the desired glycaemic control during childhood depends to a large extent on the family support and the parents' knowledge about the management and control of diabetes [8,9]. Interaction between the parents and their children is generally agreed to be a major factor in the glycaemic management [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achievement of the desired glycaemic control during childhood depends to a large extent on the family support and the parents' knowledge about the management and control of diabetes [8,9]. Interaction between the parents and their children is generally agreed to be a major factor in the glycaemic management [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These factors would appear to be obvious determinants of health. The reports of the relationship between glycaemic control and social determinants are controversial, but most researchers identify association between them [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…What are the mediating factors? The literature identifies a few strong 'candidates' that seem relevant within the context of diabetes monitoring and care, chief among them are: Perceived control, self-efficacy, stress regulation and management, and conflict management and resolution [18,19]. All these have been explored in psychological research and identified as underlying mechanisms accounting for a broad range of performance and behavior change.…”
Section: A Brief Discussion and Directions For Future Researchmentioning
confidence: 99%
“…Another preliminary result suggests that the levels of EI among a small sample of adult diabetics' spouses associated favorably with their care outcomes, even after controlling for background variables and the patients' own levels of EI partly reported in [17]. In a recent review of the literature on the support of families of children with type 2 diabetes, though not always directly related to the concept of EI, evidence quoted supported associations between family caregivers' emotional abilities and coping skills and their children's diabetic management outcome indicators [18].…”
Section: The Association In a Broader Context ?mentioning
confidence: 99%
“…1.2.1 Care of child Type 1 diabetes, asthma and eczema. Children with chronic illness are young and therefore not yet able to self-care and manage their illness (Beacham & Deatrick, 2013;Zysberg & Lang, 2015). Until they become more independent and develop the ability to self-care parents need to take on the main responsibilities related to their child's illness management (American Diabetes Association, 2013; Sullivan-Bolyai, Deatrick, Gruppuso, Tamborlane, & Grey, 2002).…”
Section: Parent Experiencesmentioning
confidence: 99%